Implikasi Keterampilan Digital terhadap Profesionalisme Guru UPT Satuan Pendidikan SDN Pager dalam Menghadapi Disrupsi Pendidikan - Munawaroh, Faizatul; Mardhatillah; Suciptaningsih, Oktaviani Adhi; Nusantara, Toto (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Digital transformation in education has required teachers to develop digital skills to enhance the quality of learning and their professionalism. This study aims to explore the level of digital skills, the application of technology in teaching, and the challenges faced by teachers at UPT Satuan Pendidikan SDN Pager II. A qualitative descriptive approach was employed, utilizing data collection techniques such as surveys, classroom observations, semi-structured interviews, and document analysis. The results reveal a significant gap in teachers' digital skills. Approximately 40% of teachers lack adequate proficiency in using digital tools, while the remaining 60% exhibit varying levels of competence, ranging from basic to advanced. Although most teachers have integrated technology into their teaching, its use remains limited to simple activities such as document creation or sourcing learning materials. Only 20% of teachers leverage technology to create interactive learning experiences. Major challenges include limited access to technological devices, insufficient ongoing training, and time constraints due to heavy workloads. These findings highlight the need for relevant and sustainable training programs, adequate technological infrastructure, and the development of learning communities to support technology adoption